Fostering Economic Development Through Ukraine’s Border Guard Service: Administrative and Legal Perspectives on Contemporary Issues and Future Prospects - Tsaruk, Andrii; Kushnir, Yaroslav; Demchyk, Nadiia; Tsarenko, Olha; Tsarenko, Serhii; Adamchuk, Serhii (European Journal of Sustainable Development, 2025)
The article is devoted to the study of administrative and legal aspects of the State Border Guard Service of Ukraine during martial law. The article examines the legislative framework of the State Border Guard Service of Ukraine and the administrative and legal aspects of its functioning, which include control over compliance with customs requirements, national security, and compliance with the requirements of the law on legal border crossing. The author examines the changes in legislation that have affected the expansion of the powers of border guards and their activities, which is also due to the martial law. The author analyzes the legal aspects of border guards' control over compliance with the rules of border crossing during martial law. The author describes the functions of border guards in controlling the departure of military personnel and persons liable for military service from the State. Attention is drawn to modern devices and systems that allow identifying those crossing the border, which allows border guards to carry out their work effectively. The role of international organizations and partners in improving the functioning of the Service is also considered. The article also examines the current problems of the State Border Guard Service of Ukraine, which are caused by discrepancies in legislation and the use of illegal border crossing by violators, and also identifies bureaucracy as one of the problems of the Service's development. At the same time, the author identifies the prospects for the development of the State Border Guard Service of Ukraine, which allows us to talk about ways to improve the activities of the State Border Guard Service. Keywords: administrative and legal aspect, martial law, State Border Guard Service of Ukraine, legislation, border, offender, Service